2017
DOI: 10.1002/2016jc012664
|View full text |Cite
|
Sign up to set email alerts
|

Open‐ocean convection process: A driver of the winter nutrient supply and the spring phytoplankton distribution in the Northwestern Mediterranean Sea

Abstract: This study was a part of the DeWEX project (Deep Water formation Experiment), designed to better understand the impact of dense water formation on the marine biogeochemical cycles. Here, nutrient and phytoplankton vertical and horizontal distributions were investigated during a deep open‐ocean convection event and during the following spring bloom in the Northwestern Mediterranean Sea (NWM). In February 2013, the deep convection event established a surface nutrient gradient from the center of the deep convecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 78 publications
3
31
0
Order By: Relevance
“…There is indeed evidence [see Séverin et al ., ] that nutrients concentrations are altered by the resuspension of deep sediment. Séverin et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is indeed evidence [see Séverin et al ., ] that nutrients concentrations are altered by the resuspension of deep sediment. Séverin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Séverin et al . [] showed that during the winter cruise (DEWEX 1), in the absence of enhanced primary production, N and P concentrations for fully mixed stations are slightly larger than for stations where the mixing only affects part of the water column. This is notably expressed in the strong reduction of the N/P stoichiometric ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the stronger and longer winter mixing in the “High Bloom” bioregion could have enhanced silicates availability, generating more favorable conditions for diatoms, and leading to the development of an enhanced diatom spring bloom. Severin et al [] showed that the DEWEX ship surveys stations performed in February 2013 inside the deep convection area presented higher surface [Si(OH) 4 ] and higher silicates to nitrates (Si:N) ratio ([Si(OH) 4 ] ∼ 7.1 µM and Si:N ∼ 0.86) than the ship surveys stations performed in the surrounding mixed area ([Si(OH) 4 ] ∼ 3.63 µM and Si:N ∼0.70).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, and in the framework of the MerMex project, four cruises were carried out between July 2012 and June 2013 (Estournel et al, 2016b;Waldman et al, 2016). The data that were collected made it possible to describe the spatial distribution of phytoplankton in the deep convection northwestern Mediterranean during stratified, deep convection, and phytoplankton bloom periods (Mayot et al, 2017a;Severin et al, 2017). This unprecedented in situ observation offered a great opportunity to calibrate and validate a 3-D coupled physical-biogeochemical model (Estournel et al, 2016a;Kessouri et al, 2017).…”
Section: 1002/2016jc012669mentioning
confidence: 99%